Evaluación de fertilizantes compuestos de síntesis química, en cultivares de arroz (Oryza sativa L.)”. En la zona de Puebloviejo - Vera Engracia, Juana Alexandra (2019)
VIII. SUMMARY The application of nutrients to soils is of vital importance in modern crop production methods. This project evaluated the agronomic behavior of rice cultivars to the application of chemical synthesis fertilizers, determined the best treatment and dosage of application, and had an economic analysis in relation to the benefit / cost. The present research work was carried out in the farm "5 Hermanos" belonging to the Las Guaijas 2 Campus, in the Puerto Pechiche parish of Pueblo Viejo Canton, at Kilometer 35.3 of the Puerto Pechiche-Pueblo Viejo Road. The rice varieties INIAP-16, F-12 and FL-01 were used as the sowing material. Fertilizer treatments were with MANUCHAR ARROZ, FERTIANDINO ARROZ, FERTISA ARROZ and Urea-DAP-Muriato. In this work, the research was carried out using the experimental design divided plots with three large plots and four small plots, in three replications. During the development of the trial, the agricultural practices necessary for the normal development of the crop were used. The variables evaluated were: height of plants, number of tillers per m2, grains per panicle, length of panicles, number of panicles m2, days to flowering, days to harvest, number of grains per panicle, weight 1000 seeds, yield per hectare, foliar analysis and economic analysis. The results indicate that the applied fertilizer programs generated increases in grain yield in rice, 25% higher than Urea. The interaction of the variety INIAP-12 plus Manuchar 400 kg / ha, gave greater number of tillers and panicles. The panicles were larger in the INIAP-16 variety fertilized with Manuchar 400 kg / ha, there was more grain in the plants fertilized with Manuchar 400 kg / ha in the INIAP-16 variety. All the treatments presented similar time during the flowering and harvesting process. The highest recorded yield was presented in the INIAP-16 variety fertilized with Manuchar 400 kg / ha with 6163.3 kg / ha. The crop presented low levels of Potassium and Copper, high in Manganese, Iron, Zinc and Calcium; being variable in Nitrogen, Phosphorus and Magnesium. The INIAP-16 variety fertilized with Manuchar 400 kg / ha presented the highest net profit of $ 787.73